PENGARUH CITRA MEREK, GAYA HIDUP DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN IPHONE DIKALANGAN MAHASISWA UNIVERSITAS TEKNOLOGI SUMBAWA - Alfiansyah, Dany; Sugiarto, Aris (Jurnal Nusa Manajemen, 2025)
This research aims to examine the influence of brand image, lifestyle and product quality on iPhone purchasing decisions among Sumbawa University of Technology students. The sample in this study was selected using a purposive sampling technique, with a sample of 114 respondents. This research uses a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) data analysis method. The research results show that brand image has a positive and significant effect on purchasing decisions. Lifestyle has no influence on purchasing decisions. Meanwhile, product quality has a positive and significant influence on iPhone purchasing decisions among Sumbawa University of Technology students.